Ozone destruction on ice - Langenberg, Stefan; Schurath, Ulrich (Geophysical research letters, 1999)
The destruction of ozone on ice surfaces was studied with an ice-coated fused silica column used as a very long flow tube. Ozone destruction was found to be very slow. At 223 K and 258 K the measured reaction probabilities fall in the range 2 × 10−8 - 4 × 10−10, decreasing with increasing ozone concentration (20-1000 nbar). The observed kinetics are explained by an at least two step mechanism. The low reaction rates observed are insignificant for ozone destruction in cirrus clouds.
Gesehen am 08.10.2020